Nest architecture and parental care in Ruddy Treerunner Margarornis rubiginosus - Sánchez Pérez, Julio E. (2018)
We complement the only existing nest description for Ruddy Treerunner Margarornis rubiginosus and include observations of nestbuilding and breeding behaviour. We also compare our data with existing information on nest architecture and breeding biology of the closely related Pearled Treerunner M. squamiger and Spotted Barbtail Premnoplex brunnescens. The nest of Ruddy Treerunner was a pendant closed nest below a single tree branch and was mostly constructed of moss. In the nest base there was a circular entrance and a second cavity. The inner chamber was spherical and the egg cup was mostly constructed of roots, fern scales and other plant fibres. Both adults build the nest and care for chicks. We observed a nest helper and removal of faecal sacs by both adults. Many aspects of nest structure and parental behaviour are similar to those of its sister species, thereby supporting existing genetic data.